Economical provision of blood components for critical patient transport across a large geographic area. Issue 5 (12th February 2021) - Latimer, Andrew; Utarnachitt, Richard B.; Tuott, Erin E.; Hess, John R.
Abstract: Background: Rapid air transport of critically injured patients to sites of appropriate care can save lives. The provision of blood products on critical care transport flights may save additional lives by starting resuscitation earlier. Methods: Our regional trauma center transfusion service provided 2 units of O‐negative red blood cells and 2 units of A low‐titer anti‐B liquid plasma in an internally monitored and sealed eutectic box weighing 10.4 pounds to eight air bases once weekly. Flight crews were instructed to transfuse plasma units first. Unused blood was returned to the transfusion service. Total blood use and wastage were recorded. Results: Over a 6‐year period, ≈ 7400 blood components were provided, and >1000 were used by the air transport service in patient care. Plasma units were 57% of all units given. Unused units were returned to the providing transfusion service and used in hospital patient care with <3% loss. Estimated cost of providing blood per mission was $63 and per patient transfused was $1940. Conclusions: With appropriate attention to detail, it is possible to provide life‐saving blood components to aeromedical transport services across a large geographic area with efficient blood component usage, minimal blood wastage, and low cost.